Extração de proteínas de folha de mandioca (Manihot esculenta Crantz) para obtenção de concentrado protéico - Ferri, Priscila (2006)
The objective of this work was to evaluate the efficiencies of protein extration for attainment of proteins leaf concentrate cassava (Manihot esculenta Crantz), using seven methods of extration cited by authors CEREDA & VILPOUX (2003), CHAVES (1987), TUPINAMBÁ & VIEIRA (1979) and FASUYI & ALETOR (2005). The experiment was carried through in the dependences of the State University of the West of the Paraná campus Cascavel, in the laboratory of Sanitation of the course of Agricultural Engineering. The cassava leves had been harvested in third part of the plant with age of 12 months in a property of the city of Cascavel. For the protein extration dehydrated leves had been used, with rude protein texts in dry base of 36.55 % and humidity of 11.27%. Methods 1 and 2 cited by CEREDA & VILPOUX (2003), method 5 cited by CHAVES (1987), method 6 cited by TUPINAMBÁ & VIEIRA (1979) and method 7 of FASUYI & ALETOR (2005) had been the ones that had gotten greaters proteins texts in the concentrates, above of 50%. The biggest incomes of extration had been gotten by methods 2, 5, 6 and 7 with incomes of protein extration above of 35%. Methods 1, 2, 4 and 5 had been tested using two consecutive extrations similar to improve the losses of mass and to increase the extration income, however only occurred the reduction of the losses of mass in the process, not being then necessary the use of two phases of extration. Methods 1, 2, 4 and 5 had been compared, already applied with leves dehydrated, using cool leves. The cassava leves (Manihot esculenta Crantz) cool had been harvested in third part of the plant with age of 9 months with rude protein texts in dry base of 27.70% with 72% of humidity. It did not have difference in the extration incomes, being more advantageous to use dehydrated leves due to possess minors toxic factors and greater durability. Methods 2 and 5 had revealed alternative for attainment of cassava proteins leaf concentrates, due to extration easiness, and not to need equipment and materials that can increase the cost of protein extration, thus making possible one better exploitation of cassava leves.